Effects of Elevated Temperature on the Residual Behavior of Concrete Containing Marble Dust and Foundry Sand - Tiwary A.K.; Singh S.; Kumar R.; Chohan J.S.; Sharma S.; Singh J.; Li C.; Ilyas R.A.; Asyraf M.R.M.; Malik M.A. (MDPI, 2023)
Cements; Compressive strength; Concrete aggregates; Deterioration; Dust; Elastic moduli; Foundries; Foundry sand; Marble; Quenching; Tensile strength; Waste disposal; Water absorption; Anneal-ing; Elevated temperature; Exposed to; Fine sand; Fire exposures; Marble dust; Properties of concretes; Residual behavior; Residual properties; Residual property of concrete; Construction industry